(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background. Refractive surgery is an alternative treatment for the correction of strabismus associated with ametropia in adults. Purpose. To report a case of a young adult patient with exodeviation and uncorrected myopia in childhood who came to a consultation to improve her visual and aesthetic quality. Material and Methods. Рreoperatively, the uncorrected visual acuity of 20/400 was presented in both eyes with compound myopic astigmatism that, with correction, improved to 20/30. In addition, in both eyes the patients presented exotropia of 40º that increased to 60º. Results. Photorefractive keratectomy surgery was performed in both eyes, achieving an uncorrected visual acuity of 20/20, and orthotropia was maintained until the consultation six months after the operation. Conclusion. Refractive surgery can be performed successfully in patients with accommodative or non-accommodative strabismus. Each patient must be studied to define whether or not they are suitable for this type of surgery.